Semi-Heusler structure thermoelectric material and preparation method and application thereof

By doping Ni elements in NbRuSb to form semi-Hessler structure thermoelectric material of NbRu1-xNixSb, the problem of low intrinsic NbRuSb carrier concentration is solved, and its thermoelectric performance is significantly improved, especially showing a higher power factor at high temperatures.

CN119522018AActive Publication Date: 2025-02-25SHANGHAI UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411630619.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing NbRuSb materials have problems of low flow concentration and low electrical transport performance in the intrinsic state.

Method used

By replacing the Ru element with Ni in NbRuSb, a semi-Hessler structural thermoelectric material of NbRu1-xNixSb is formed to optimize its thermoelectric performance.

Benefits of technology

The conductivity, Seebeck coefficient and power factor of thermoelectric materials are improved, and its thermoelectric properties are enhanced, especially at 682K temperature, the power factor reaches 34.8μW·cm-1·K-2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522018A_ABST
    Figure CN119522018A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of thermoelectric materials, and particularly relates to a thermoelectric material with a half-Heusler structure and a preparation method and application thereof. The thermoelectric material is an N-type thermoelectric material formed by replacing Ru in NbRuSb with Ni elementary substance in a doped mode, the chemical formula of the thermoelectric material is NbRu1-xNixSb, and the value range of x is 0 lt; x is less than or equal to 0.1; nb elementary substances, Ru elementary substances, Ni elementary substances and Sb elementary substances are used as raw materials, and the thermoelectric material with the semi-Heusler structure is prepared by adopting methods of high-energy ball milling, spark plasma sintering and annealing. The material can be applied to manufacturing of thermoelectric devices. Compared with the prior art, the thermoelectric material prepared by the invention optimizes the thermoelectric performance of the thermoelectric material with the half-Heusler structure, the NbRu0. 9Ni0. 1Sb has the highest thermoelectric performance, the power factor reaches up to 34.8 mu W.cm <-1 >. K <-2 > at the temperature of 682K, and the zT is 0.404 at the temperature of 982K.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermoelectric materials, and in particular relates to a half-Heusler structure thermoelectric material and a preparation method and application thereof. Background Art

[0002] Energy, materials, and information are the three pillars of human development. Modern human civilization, developed since the Industrial Revolution, has relied heavily on fossil fuels, primarily coal, oil, and natural gas. However, these energy sources are not inexhaustible. As society develops, the demand for energy increases, and non-renewable fossil fuels are facing a resource shortage. As fossil fuels become increasingly depleted, in addition to promoting the use of renewable clean energy sources such as solar, wind, and hydropower, the development of clean and reliable energy conversion technologies is gaining widespread attention. Modern industry is highly energy-intensive and also generates significant energy waste. As a type of energy conversion material, thermoelectric materials can effectively recycle waste heat from industrial waste, automotive engines, and exhaust gases, playing a significant role in improving energy efficiency and alleviating the energy crisis. Furthermore, thermoelectric devices are also used in household heating and cooling appliances. Therefore, thermoelectric materials can contribute to everything from sustainable social development to the convenience of daily life.

[0003] Thermoelectric materials realize the direct and reversible conversion between thermal energy and electrical energy. The conversion process includes three effects: Seebeck effect, Peltier effect and Thomson effect. The three provide a theoretical basis for the systematic study of thermoelectric materials. Thermoelectric devices have the characteristics of simple structure, no moving parts, precise temperature control, both hot and cold, and no gas or liquid working medium. Thermoelectric materials include many material systems, and different temperature application scenarios can find matching materials with excellent thermoelectric performance and thermal stability. The size of the dimensionless thermoelectric figure of merit zT measures the energy conversion efficiency of thermoelectric materials, zT = S 2 σT / κ, where S, σ, κ, and T are the Seebeck coefficient, electrical conductivity, thermal conductivity, and absolute temperature of the environment, respectively.

[0004] Half-Heusler alloys are a type of medium-to-high-temperature thermoelectric material with excellent mechanical properties and thermal stability at high temperatures. Their chemical formula can be written as ABX. Research on this type of thermoelectric material can usually be distinguished by its valence electron number. Summary of the Invention

[0005] The purpose of the present invention is to provide a half-Heusler structure thermoelectric material and its preparation method and application in order to solve at least one of the above problems. By replacing the lattice site originally occupied by Ru with the doping element Ni, the low carrier concentration and low electrical transport performance of the NbRuSb material in the intrinsic state in the prior art are solved. The pure phase of the half-Heusler structure is prepared through a shorter preparation process, and the thermoelectric performance of the half-Heusler structure thermoelectric material is optimized.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] One of the technical solutions of the present invention is to provide a half-Heusler structure thermoelectric material, which is an N-type thermoelectric material formed by replacing Ru in NbRuSb. Its chemical formula is NbRu 1-x Ni x Sb, where x ranges from 0 <x≤0.1。

[0008] Furthermore, the NbRu 1-x Ni x In Sb, the value of x is selected from any one of 0.02, 0.04, 0.06, 0.08 and 0.1.

[0009] Furthermore, the electrical conductivity of the thermoelectric material is in the range of 1770-80700 S·m -1 The Seebeck coefficient is between (-340)-(-160)μV·K -1 The power factor is between 1.1-34.9μW·cm -1 ·K -2 The thermal conductivity is between 5.72-11.91W·m -1 ·K -1 The zT value is between 0.003-0.404.

[0010] Furthermore, when the value of x is 0.1, NbRu 0.9 Ni 0.1 The highest power factor of Sb at 682K is 23μW·cm -1 ·K -2 .

[0011] The second technical solution of the present invention is to provide a method for preparing the half-Heusler structure thermoelectric material as described above, using Nb, Ru, Ni and Sb as raw materials, and adopting high-energy ball milling, spark plasma sintering and annealing methods to prepare the half-Heusler structure thermoelectric material.

[0012] Furthermore, the preparation method comprises the following steps:

[0013] S1: Sample preparation: According to the stoichiometric ratio of Nb:Ru:Ni:Sb=1:(1-x):x:1, weigh Nb, Ru, Ni and Sb, where x ranges from 0 <x≤0.1;

[0014] S2: Alloying: High-energy ball milling of the element weighed in step S1;

[0015] S3: Sintering: Spark plasma sintering the mixed powder obtained by high-energy ball milling in step S2;

[0016] S4: vacuum sealing: vacuum sealing the material sintered in step S3;

[0017] S5: Annealing: The tube after vacuum sealing in step S4 is subjected to high-temperature annealing, and the half-Heusler thermoelectric material is obtained after cooling.

[0018] Furthermore, the total amount of raw materials prepared in step S1 is 0.02 mol, and the required mass of each element can be calculated by the formula m=n×M (n: the required molar amount of an element under a specific composition, m: the required mass, M: the atomic molar mass) and the stoichiometric ratio of the corresponding components.

[0019] Furthermore, in step S1, the Nb element, Ru element, Ni element, and Sb element are respectively elemental Nb sheets, Ru powder, Ni sheets, and Sb particles.

[0020] Furthermore, in step S1, the weighed elements are placed in a stainless steel ball mill under an inert gas environment.

[0021] Furthermore, in step S2, the high-energy ball milling time is 20-24 hours.

[0022] Furthermore, in step S2, the single substance is subjected to long-term continuous ball milling and material collision in a high-energy ball mill to obtain a mixed powder.

[0023] Furthermore, the samples in steps S1 and S2 and the mixed powder obtained by ball milling are stored in an inert gas environment.

[0024] Furthermore, the inert gas is argon.

[0025] Furthermore, in step S3, the spark plasma sintering includes the following steps: placing the mixed powder obtained by ball milling in a graphite mold and evacuating the mixture, then applying a pressure of 3.5-4 kN to the powder through the graphite mold, and then starting sintering. The sintering gas pressure is 50-60 MPa, and the temperature is increased to 850°C at a heating rate of 30-50°C / min, and then the temperature is kept warm for 10-15 minutes. Then, the applied pressure is removed and the powder is naturally cooled to room temperature to obtain a block material.

[0026] Furthermore, in step S4, the vacuum sealing process includes: placing the sintered material into a quartz tube, connecting the quartz tube to a tube sealing device, sealing the quartz tube using the tube sealing device, evacuating and filling the tube for 3-5 cycles, washing the air, evacuating the tube to less than 3Pa, and strongly heating the quartz plug with a high-temperature hydrogen-oxygen flame to soften the quartz tube and vacuum-encapsulate the material.

[0027] Furthermore, in step S5, the quartz tube is placed in a muffle furnace for annealing.

[0028] Furthermore, in step S5, the annealing temperature of the high temperature annealing is 800-850K, the heating rate is 1-2°C / min, and the annealing is carried out for 3-7 days and then the annealing is carried out in the furnace.

[0029] A third technical solution of the present invention is to provide an application of the above-mentioned half-Heusler structure thermoelectric material in the manufacture of thermoelectric devices.

[0030] The present invention first prepares a pure phase of NbRuSb, a thermoelectric material with an 18-valence electron half-Heusler structure, and tests its intrinsic thermoelectric properties. The results reveal that the intrinsic NbRuSb exhibits N-type conductivity, low electrical conductivity, a high Seebeck coefficient, and high thermal conductivity. Half-Heusler structures with 18 valence electrons can generally be synthesized stably, exhibiting the physical properties of semiconductors with a separation of bonding and antibonding states, and exhibit high power factor and high thermal conductivity. To improve the low carrier concentration of intrinsic NbRuSb, the present invention employs Ni, which has a higher valence electron count, to replace doped Ru to adjust the carrier concentration. The goal is to develop a half-Heusler thermoelectric material with high thermoelectric performance, particularly a high power factor.

[0031] On the basis of conforming to the common sense in this field, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] 1. The novel half-Heusler structure thermoelectric material prepared by the present invention is an N-type thermoelectric material formed by doping NbRuSb and Ni. Its chemical formula is NbRu 1-x Ni x Sb, by replacing the doping Ni element in the lattice site originally occupied by Ru, optimizes the thermoelectric performance of the new half-Heusler structure thermoelectric material. 0.9 Ni 0.1 Sb has the highest thermoelectric performance, with a power factor of up to 34.8 μW·cm at 682K. -1 ·K -2 , at a temperature of 982K, zT is 0.404.

[0034] 2. The process of preparing the novel semi-Heusler structure thermoelectric material of the present invention includes high energy ball milling (HEBM), spark plasma sintering (SPS) and annealing to prepare a pure phase with a semi-Heusler structure. The material prepared by the present invention contains significantly less impurities than other methods, and the process flow of the method is short, the operation is simple, and it is easy to implement.

[0035] 3. The electrical conductivity of the compounds in the novel half-Heusler structure thermoelectric material prepared by the present invention shows different change patterns with the increase of carrier concentration, indicating the effectiveness of substitutional doping as a strategy for optimizing thermoelectric performance.

[0036] 4. The novel half-Heusler structure thermoelectric material prepared by the present invention optimizes the thermoelectric performance of the material and obtains a higher power factor, providing a promising approach for further reducing the thermal conductivity of the material and improving the zT value. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 NbRu in Examples 1-6 of the present invention 1-x Ni x Schematic diagram of the structural formula of Sb-based thermoelectric materials.

[0038] Figure 2 NbRu in Examples 1-6 of the present invention 1-x Ni x X-ray diffraction patterns of Sb-based thermoelectric materials.

[0039] Figure 3 This is the X-ray diffraction pattern of the NbRuSb-based thermoelectric material in Comparative Example 1.

[0040] Figure 4 NbRu in Examples 1-6 of the present invention 1-x Ni x Schematic diagram of the conductivity curve of Sb-based thermoelectric materials varying with temperature.

[0041] Figure 5 NbRu in Examples 1-6 of the present invention 1-x Ni x Schematic diagram of room-temperature carrier concentration of Sb-based thermoelectric materials.

[0042] Figure 6 NbRu in Examples 1-6 of the present invention 1-x Ni x Schematic diagram of the Seebeck coefficient curve of Sb-based thermoelectric materials as a function of temperature.

[0043] Figure 7 NbRu in Examples 1-6 of the present invention 1-x Ni xSchematic diagram of the power factor curve of Sb-based thermoelectric materials varying with temperature.

[0044] Figure 8 NbRu in Examples 1-6 of the present invention 1-x Ni x Schematic diagram of the thermal conductivity curve of Sb-based thermoelectric materials varying with temperature.

[0045] Figure 9 NbRu in Examples 1-6 of the present invention 1-x Ni x Schematic diagram of the curve of zT value of Sb-based thermoelectric materials changing with temperature. DETAILED DESCRIPTION

[0046] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0047] Unless otherwise specified, the experimental reagents and raw materials used in the present invention are commercially available.

[0048] The experimental methods without specific conditions in the following implementations are all based on conventional methods and conditions, or selected according to the product specifications. Unless otherwise specified, the experimental instruments used in the present invention are all conventional laboratory instruments.

[0049] Example 1

[0050] This embodiment provides a thermoelectric material with a half-Heusler structure, specifically an N-type thermoelectric material formed by doping NbRuSb and Ni, and its chemical formula is NbRuSb.

[0051] In addition, this embodiment also provides a method for preparing a thermoelectric material NbRuSb with a half-Heusler structure, which is synthesized by high energy ball milling (HEBM), spark plasma sintering (SPS) and annealing. The specific steps are as follows:

[0052] S1: Calculation: Based on the stoichiometric ratio of Nb:Ru:Ni:Sb = 1:1:0:1 and the formula m = n × M, calculate the mass of each element required to produce 0.02 mol of NbRuSb.

[0053] S2: Sample preparation: In an argon glove box, weigh 99.95% pure Nb flakes, 99.95% pure Ru powder, and 99.999% pure Sb particles on an electronic balance with an accuracy of 0.1 mg according to the masses calculated in step S1, and place the weighed raw materials in a stainless steel ball mill;

[0054] S3: Alloying: placing the ball mill jar in step S2 in a high-energy ball mill, and obtaining a mixed powder by continuous and uninterrupted collision between the balls and the material for 20 hours;

[0055] S4: Sintering: The mixed powder obtained in step S3 is stored in an argon glove box, and 0.8-1.0 g of the powder is weighed and placed in a graphite mold with a diameter of 10 mm. The mold is then placed in a spark plasma sintering device and evacuated. Subsequently, pressure is slowly applied to the sample to 50 MPa to start sintering. The sintering rate is 20-30 ° C / min and reaches 850 ° C in 30 minutes. Finally, the heat is kept for 10-15 minutes, and then the pressure is removed and naturally cooled to room temperature to obtain a block material with a diameter of 10 mm and a thickness of 0.9-1.5 mm;

[0056] S5: Vacuum sealing: Place the sintered bulk material into a quartz tube and then perform vacuum sealing. The specific process is to connect the quartz tube to the tube sealing device, seal the quartz tube with the tube sealing device, evacuate and refill the tube five times, purge the gas, and evacuate the tube to less than 3Pa. Use a high-temperature hydrogen-oxygen flame to strongly heat the quartz plug to soften the quartz tube and vacuum seal the bulk material.

[0057] S6: Annealing: The vacuum-sealed quartz tube was placed in a muffle furnace for annealing at a temperature of 850°C, a heating rate of 2°C / min, and kept at this temperature for 3 days. The furnace was then cooled, and finally the NbRuSb test material was obtained.

[0058] Example 2

[0059] This embodiment provides a thermoelectric material with a half-Heusler structure, specifically an N-type thermoelectric material formed by doping NbRuSb and Ni, whose chemical formula is NbRu 0.98 Ni 0.02 Sb, its structural formula is as follows Figure 1 shown.

[0060] In addition, this embodiment also provides a half-Heusler structure thermoelectric material NbRu 0.98 Ni 0.02 The preparation method of Sb is synthesized by high energy ball milling (HEBM), spark plasma sintering (SPS) and annealing. The specific steps are as follows:

[0061] S1: Calculation: Based on the stoichiometric ratio of Nb:Ru:Ni:Sb=1:0.98:0.02:1 and the formula m=n×M, calculate 0.02 mol NbRu 0.98 Ni 0.02 The mass of each element required for Sb;

[0062] S2: Sample preparation: In an argon glove box, weigh 99.95% pure Nb sheets, 99.95% pure Ru powder, 99.95% pure Ni sheets, and 99.999% pure Sb particles on an electronic balance with an accuracy of 0.1 mg according to the masses calculated in step S1, and place the weighed raw materials in a stainless steel ball mill;

[0063] S3: Alloying: placing the ball mill jar in step S2 in a high-energy ball mill, and obtaining a mixed powder by continuous and uninterrupted collision between the balls and the material for 20 hours;

[0064] S4: Sintering: The mixed powder obtained in step S3 is stored in an argon glove box, and 0.8-1.0 g of the powder is weighed and placed in a graphite mold with a diameter of 10 mm. The mold is then placed in a spark plasma sintering device and evacuated. Subsequently, pressure is slowly applied to the sample to 50 MPa to start sintering. The sintering rate is 20-30 ° C / min and reaches 850 ° C in 30 minutes. Finally, the heat is kept for 10-15 minutes, and then the pressure is removed and naturally cooled to room temperature to obtain a block material with a diameter of 10 mm and a thickness of 0.9-1.5 mm;

[0065] S5: Vacuum sealing: Place the sintered bulk material into a quartz tube and then perform vacuum sealing. The specific process is to connect the quartz tube to the tube sealing device, seal the quartz tube with the tube sealing device, evacuate and refill the tube five times, purge the gas, and evacuate the tube to less than 3Pa. Use a high-temperature hydrogen-oxygen flame to strongly heat the quartz plug to soften the quartz tube and vacuum seal the bulk material.

[0066] S6: Annealing: The vacuum-sealed quartz tube was placed in a muffle furnace for annealing at a temperature of 850°C, a heating rate of 2°C / min, and kept at this temperature for 3 days. The furnace was then cooled, and finally the NbRuSb test material was obtained.

[0067] Example 3

[0068] This embodiment is basically the same as the aforementioned embodiment 2, with the following special features:

[0069] This embodiment provides a thermoelectric material with a half-Heusler structure, specifically an N-type thermoelectric material formed by doping NbRuSb and Ni, whose chemical formula is NbRu 0.96 Ni 0.04 Sb.

[0070] In addition, this embodiment also provides a half-Heusler structure thermoelectric material NbRu 0.96 Ni 0.04The preparation method of Sb is synthesized by high energy ball milling (HEBM), spark plasma sintering (SPS) and annealing. Except that in step S1, Nb:Ru:Ni:Sb=1:0.96:0.04:1, the remaining steps are the same as those in Example 2.

[0071] Example 4

[0072] This embodiment is basically the same as the aforementioned embodiment 2, with the following special features:

[0073] This embodiment provides a thermoelectric material with a half-Heusler structure, specifically an N-type thermoelectric material formed by doping NbRuSb and Ni, whose chemical formula is NbRu 0.94 Ni 0.06 Sb.

[0074] In addition, this embodiment also provides a half-Heusler structure thermoelectric material NbRu 0.94 Ni 0.06 The preparation method of Sb is synthesized by high energy ball milling (HEBM), spark plasma sintering (SPS) and annealing. Except that in step S1, Nb:Ru:Ni:Sb=1:0.94:0.06:1, the remaining steps are the same as those in Example 2.

[0075] Example 5

[0076] This embodiment is basically the same as the aforementioned embodiment 2, with the following special features:

[0077] This embodiment provides a thermoelectric material with a half-Heusler structure, specifically an N-type thermoelectric material formed by doping NbRuSb and Ni, whose chemical formula is NbRu 0.92 Ni 0.08 Sb.

[0078] In addition, this embodiment also provides a half-Heusler structure thermoelectric material NbRu 0.98 Ni 0.02 The preparation method of Sb is synthesized by high energy ball milling (HEBM), spark plasma sintering (SPS) and annealing. Except that in step S1, Nb:Ru:Ni:Sb=1:0.92:0.08:1, the remaining steps are the same as those in Example 2.

[0079] Example 6

[0080] This embodiment is basically the same as the aforementioned embodiment 2, with the following special features:

[0081] This embodiment provides a thermoelectric material with a half-Heusler structure, specifically an N-type thermoelectric material formed by doping NbRuSb and Ni, whose chemical formula is NbRu 0.9 Ni0.1 Sb.

[0082] In addition, this embodiment also provides a half-Heusler structure thermoelectric material NbRu 0.9 Ni 0.1 The preparation method of Sb is synthesized by high energy ball milling (HEBM), spark plasma sintering (SPS) and annealing. Except that in step S1, Nb:Ru:Ni:Sb=1:0.9:0.1:1, the remaining steps are the same as those in Example 2.

[0083] Comparative Example 1

[0084] This comparative example is a thermoelectric material prepared by conventional methods in the prior art. Its chemical formula is NbRuSb. The specific preparation method is described in the paper [Ternary transition metal antimonides and bismuthides with MgAgAs-type and filled NiAs-type structure, 1996].

[0085] The ratios of the elements in Examples 1-6 and Comparative Example 1 are shown in Table 1:

[0086] Table 1 Ratios of elements in thermoelectric materials of Examples 1-6 and Comparative Example 1

[0087] Nb Ru Ni Sb Example 1 1 1 0 1 Example 2 1 0.98 0.02 1 Example 3 1 0.96 0.04 1 Example 4 1 0.94 0.06 1 Example 5 1 0.92 0.08 1 Example 6 1 0.9 0.1 1 Comparative Example 1 1 1 0 1

[0088] Then, Examples 1-6 and Comparative Example 1 were tested and analyzed:

[0089] (1) The thermoelectric materials obtained in Examples 1 to 6 and Comparative Example 1 were measured on a Rigaku SmartLab-II diffractometer to obtain X-ray diffraction patterns. The X-ray source used in the test was Cu-K α , and the test sample is in powder state, the results are as follows Figure 2 shown.

[0090] (2) The thermoelectric materials obtained in Examples 1 to 6 were subjected to electrical performance tests using an ULVAC-RIKO ZEM-3 device. The test data included electrical conductivity and Seebeck coefficient.

[0091] (3) The thermoelectric materials obtained in Examples 1 to 6 were subjected to thermal performance tests on a NETZSCH LFA 457 device, primarily testing the thermal diffusion coefficient D.

[0092] The thermal conductivity calculation formula is κ=DC p ρ, where C p is the heat capacity of the material, which can be estimated by the Dulong-Petit law, and ρ is the material density, which can be estimated by the Archimedean drainage method.

[0093] (4) The thermoelectric materials obtained in Examples 1 to 6 were subjected to room temperature carrier concentration testing on a physical property measurement system (PPMS).

[0094] Figure 2 and Figure 3 NbRu in Examples 1-6 of the present invention respectively 1-x Ni x X-ray diffraction patterns of Sb-based thermoelectric materials and NbRuSb thermoelectric materials in Comparative Example 1. Figure 2-3 It can be seen that the NbRu prepared in the present invention 1-x Ni x The Sb-based thermoelectric material has less impurity phases. Comparing the images of NbRuSb in Comparative Example 1 with those in Example 1, it is found that the material prepared in the present invention has less impurity phase peaks.

[0095] Figure 4-9 Graph showing the thermoelectric performance test results of the thermoelectric materials obtained in Examples 1-6.

[0096] Depend on Figure 4 It can be seen that the conductivity of all tested samples increases with the increase of Ni doping amount. For samples with x = 0, 0.02, and 0.04, the conductivity increases with the increase of temperature, showing the typical change characteristics of semiconductors; for samples with x = 0.06, 0.08, and 0.1, the conductivity shows a completely different change pattern, first increasing and then decreasing with increasing temperature.

[0097] Depend on Figure 5 It can be seen that the carrier concentration of all samples increases with the increase of Ni doping amount.

[0098] Depend on Figure 6 It can be seen that the Seebeck coefficients of the test samples of Examples 1-6 are all negative, that is, Examples 1-6 are all N-type conduction dominated by electrons. The absolute value of the Seebeck coefficient decreases with the increase of Ni doping amount, and first decreases and then increases with the increase of temperature.

[0099] Depend on Figure 7 It can be seen that the power factors of all samples increase with the increase of Ni doping amount, and first increase and then decrease with the increase of temperature.

[0100] Depend on Figure 8 It can be seen that the thermal conductivity of all samples decreases monotonically with temperature. The thermal conductivity of samples with x = 0.02 and 0.04 is slightly lower than that of NbRuSb with x = 0. The thermal conductivity of samples with x = 0.06, 0.08, and 0.1 is equal to or even slightly higher than that of NbRuSb with x = 0. This is due to the significantly increased carrier concentration, which leads to an increased contribution of electrons to thermal conductivity.

[0101] Depend on Figure 9 It can be seen that the thermoelectric figures of merit zT of all samples increase with the increase of Ni doping amount.

[0102] According to the test results, it can be seen that with the increase of Ni doping content, the thermoelectric performance gradually increases, among which NbRu 0.9 Ni 0.1 The Sb compound showed the best performance: the conductivity was 50000-81000 S·m -1 Seebeck coefficient is between (-240)-(-165)μV·K -1 Between; power factor is 21-35μW·cm -1 ·K -2 Thermal conductivity is between 6.14-11.91W·m -1 ·K -1 The zT value is between 0.06 and 0.40. Thanks to the large overall power factor, the thermoelectric performance of the material is greatly improved.

[0103] In summary, the present invention can efficiently synthesize NbRu by using high-energy ball milling and spark plasma sintering method and annealing. 1-x Ni x Sb (x = 0, 0.02, 0.04, 0.06, 0.08, 0.1) is a pure phase semi-Heusler structure thermoelectric material with a high power factor. 0.9 Ni 0.1 The Sb sample has the highest thermoelectric performance, with a maximum power factor of 34.8 μW·cm at 682 K. -1 ·K -2 , at a temperature of 982K, the highest zT is 0.404.

[0104] The above description of the embodiments is intended to facilitate understanding and use of the invention by those skilled in the art. It will be apparent that those skilled in the art can readily make various modifications to these embodiments and apply the general principles described herein to other embodiments without requiring inventive effort. Therefore, the present invention is not limited to the above-described embodiments. Improvements and modifications made by those skilled in the art based on the disclosure of the present invention, without departing from the scope of the present invention, should be within the scope of protection of the present invention.

Claims

1. A half-Heusler structure thermoelectric material, characterized in that: The thermoelectric material is an N-type thermoelectric material formed by doping Ni with a single substance to replace Ru in NbRuSb, and its chemical formula is NbRu 1-x Ni x Sb, where x ranges from 0 <x≤0.1。 2. A half-Heusler structure thermoelectric material according to claim 1, characterized in that: The NbRu 1-x Ni x In Sb, the value of x is selected from any one of 0.02, 0.04, 0.06, 0.08 and 0.

1.

3. A half-Heusler structure thermoelectric material according to claim 1, characterized in that: The electrical conductivity of the thermoelectric material is between 1770 and 80700 S·m -1 The Seebeck coefficient is between (-340)-(-160)μV·K -1 The power factor is between 1.1-34.9μW·cm -1 ·K -2 The thermal conductivity is between 5.72-11.91 W·m -1 ·K -1 The zT value is between 0.003-0.

404.

4. A method for preparing a half-Heusler structure thermoelectric material as claimed in claim 1, characterized in that: With Nb, Ru, Ni and Sb as raw materials, half-Heusler structure thermoelectric materials are prepared by high-energy ball milling, spark plasma sintering and annealing.

5. The method for preparing a half-Heusler structure thermoelectric material according to claim 4, characterized in that: The preparation method comprises the following steps: S1: Sample preparation: According to the stoichiometric ratio of Nb:Ru:Ni:Sb=1:(1-x):x:1, weigh the Nb element, Ru element, Ni element and Sb element, where x ranges from 0 <x≤0.1; S2: alloying: high-energy ball milling the single substance weighed in step S1; S3: sintering: spark plasma sintering the mixed powder obtained by high energy ball milling in step S2; S4: vacuum sealing: vacuum sealing the material sintered in step S3; S5: Annealing: The tube after vacuum sealing in step S4 is subjected to high temperature annealing, and the half-Heusler thermoelectric material is obtained after cooling.

6. The method for preparing a half-Heusler structure thermoelectric material according to claim 5, characterized in that: In step S2, the high energy ball milling time is 20-24 hours.

7. The method for preparing a half-Heusler structure thermoelectric material according to claim 5, characterized in that: The samples in steps S1 and S2 and the mixed powder obtained by ball milling are stored in an inert gas environment.

8. The method for preparing a half-Heusler structure thermoelectric material according to claim 5, characterized in that: In step S3, the spark plasma sintering includes the following steps: placing the mixed powder obtained by ball milling in a graphite mold and evacuating the mixture, then applying a pressure of 3.5-4kN to the powder through the graphite mold, and then starting sintering. The sintering gas pressure is 50-60MPa, and the temperature is increased to 850°C at a heating rate of 30-50°C / min, and then the temperature is kept at 10-15min, and then the applied pressure is removed and the mixture is naturally cooled to room temperature to obtain a block material.

9. The method for preparing a half-Heusler structure thermoelectric material according to claim 5, characterized in that: In step S5, the annealing temperature of high temperature annealing is 800-850K, the heating rate is 1-2°C / min, and the furnace is cooled after keeping the temperature for 3-7 days.

10. Use of the half-Heusler structure thermoelectric material according to claim 1 in the manufacture of thermoelectric devices.

Citation Information

Patent Citations

  • Thermoelectric material and its manufacturing method

    JP2006165125A

  • Thermoelectric material and its manufacturing method

    JP2008311247A

  • Electrode active material, and metal secondary battery comprising negative electrode containing the electrode active material

    JP2012174535A

  • Thermoelectric conversion material, and thermoelectric conversion module arranged by use thereof

    JP2018019014A

  • Intermetallic compound powder producing method, intermetallic compound sintered body producing method, intermetallic compound powder, intermetallic compound sintered body, and thermoelectric conversion element

    JP2023168007A